Numerical investigation of vertical spacing effects on flame behaviour and NOx emissions in hydrogen micromix injector pairs - González López, Guillermo; Singh, Gaurav; Sethi, Vishal; Cadrecha Robles, David; Romero Vega, Pedro (American Society of Mechanical Engineers (ASME), 2025)
Hydrogen is emerging as a promising alternative to meet the aviation industry’s ambitious CO2 reduction targets. Its wide flammability limits enable lean combustion with low thermal NOx emissions, but challenges such as auto-ignition and flashback risks become a significant issue due to hydrogen’s high diffusivity and burning velocity. Micromix combustion addresses these challenges through a jet-in-crossflow configuration, generating miniaturised diffusion flames that enhance fuel-air mixing, reduce thermal NOx, and mitigate flashback. Previous studies have focused on characterising air/hydrogen mixtures, improving numerical model predictions, and exploring key design parameters such as the momentum flux ratio and air gate geometry. This study evaluates the blockage ratio (BR), a parameter that controls the vertical separation between injectors and has not been studied in isolation. Specifically, the work examines how this parameter impacts recirculation zones, flame behaviour, and NOx emissions. Using RANS simulations with the FGM combustion model together with a thermal NO post-processing tool, variations in injector spacing were analysed while maintaining constant energy density and momentum flux ratio. Key findings indicate that increasing injector separation reduces flame interaction, lowering thermal NOx emissions, while excessive separation intensifies recirculation zones, increasing NOx. The optimal blockage ratio balances these competing effects, achieving up to 15% NOx reduction under varied conditions. These insights offer valuable design recommendations for low-emission hydrogen combustion systems.
Keywords: Hydrogen; Micromix; NOx Formation; Combustion; Injector Design; 40 Engineering; 4017 Mechanical Engineering; 4002 Automotive Engineering; 13 Climate Action